Pengaruh Kualitas Produk, Kualitas Pelayanan, Harga Dan Lokasi Terhadap Keputusan Pembelian Di Soto Ayam Pak No Bok Ijo Bok Ijo Kediri - Eka Hadiwijaya; Zaenul Muttaqien; Udik Jatmiko (Politeknik Kampar, 2023)
This study discusses product quality, service quality, price and location on purchasing decisions at “Soto Ayam Pak No Bok Ijo Bok ijo Kediri”, this study aims to determine the results of the influence of product quality, service quality, price and location on purchasing decisions at “Soto Ayam Pak No Bok Ijo Bok ijo Kediri”. The method used in this study is a quantitative descriptive method. Data collection techniques in this study used primary data (observation, interviews, questionnaires) and secondary (literary study). Sampling in this study used the Accidental Sampling technique which took respondents as a sample based on coincidence, that is, anyone who met the researcher by chance could be used as a sample if the person he met was suitable as a data source. Total population in this study ± 1500 people and a sample of 94 people. Data processing in this study is using validity test, reliability test, classical assumption test, multiple linear regression, coefficient of determination (R2). The result of this research is product quality has an influence on purchasing decisions with a significant value of 0 < 0.05. Service quality has no relationship to purchasing decisions with a significant value of 0.09 > 0.05. Price has a relationship with purchasing decisions with a significant value of 0.008 <0.05. Location has no relationship to purchasing decisions with a significant value of 0.091 > 0.05.